1997
DOI: 10.1152/jappl.1997.82.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Lung liquid production rates and volumes do not decrease before labor in healthy fetal sheep

Abstract: Previous studies have suggested that the volume and production rate of fetal lung liquid decrease late in gestation, before the onset of labor, in preparation for the clearance of lung liquid at birth. In contrast, our earlier studies have not shown a decrease in lung liquid volume near term, although these studies were not continued to the onset of labor. Our aim was to determine the changes in lung liquid volume and production rate in fetal sheep during the last 2 wk of gestation up to the onset of labor at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…In contrast, as postural changes during labor can cause lung liquid loss [29], flexion of the fetal trunk, which increases abdominal pressure and elevates the diaphragm, are more likely to cause liquid expulsion [22,23]. …”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…In contrast, as postural changes during labor can cause lung liquid loss [29], flexion of the fetal trunk, which increases abdominal pressure and elevates the diaphragm, are more likely to cause liquid expulsion [22,23]. …”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…Experiments in the fetal lamb have shown that the lung liquid volume rises until the end of gestation, reaching a level of 50 mL/kg of fetal body weight on the day before labour 22,23 . According to these authors, the entire volume of fetal lung liquid ($250 mL) in ovine fetuses is cleared during normal labour 24 . In contrast to these studies, others have suggested that the volume 25,26 and production rate 27 of fetal lung liquid decrease up to 10 days before the onset of labour.…”
Section: Discussionmentioning
confidence: 99%
“…However, the little resistance that the chest offers when it follows the head through the birth canal makes it unlikely that 'vaginal squeeze' significantly influences liquid clearance [14,15]. Postural changes during labor can cause lung liquid loss [16] and flexion of the fetal trunk during delivery, which causes an increase of abdominal pressure and elevation of the diaphragm, are more likely to cause liquid expulsion [11,13].…”
Section: Pioneers In Pulmonary Imaging At Birthmentioning
confidence: 99%